Investigation of Plant Species with Identified Seed Oil Fatty Acids in Chinese Literature and Analysis of Five Unsurveyed Chinese Endemic Species - Li, Changsheng; Cheng, Xiaojun; Jia, Qingli; Song, Huan; Liu, Xiangling; Wang, Kai; Zhao, Cuizhu; Zhang, Yansheng; Ohlrogge, John; Zhang, Meng (Frontiers in Plant Science, 2017)
Diverse fatty acid structures from different plant species are important renewable resources for industrial raw materials and as liquid fuels with high energy density. Because of its immense geographical and topographical variations, China is a country with enormous diversity of plant species, including large numbers of plants endemic to China. The richness of this resource of species provides a wide range of fatty acids in seeds or other tissues, many of which have been identified by Chinese scientists. However, in the past, most publications describing analysis of these plants were written in Chinese, making access for researchers from other countries difficult. In this study, we investigated reports on seed and fruit oil fatty acids as described in Chinese literature. Six books and more than one thousand papers were collected and the identified fatty acids and relevant plant species were summarized. In total, about 240 fatty acids from almost 1,500 plant species were identified from available Chinese literature. Only about one third of these species were retrieved in in the PhyloFAdb and SOFA online databases of plant fatty acids. By referring to a summary of plant species endemic to China, 277 Chinese endemic species from 68 families have been surveyed for seed fatty acids. These account for less than 2% of total Angiosperm species endemic to China indicating the scope of species yet to be surveyed. To discover additional new fatty acid structures that might benefit society, it is important in the future to study oilseed fatty acids of the many other Chinese endemic plants. As an example, seeds of five unsurveyed species were collected and their fatty acids were analyzed. Ricinoleic acid was detected for the first time in the Salicaceae family.